2020
DOI: 10.1016/j.gca.2020.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotope fractionation between aqueous and carbonate-associated sulfate in abiotic calcite and aragonite

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 101 publications
5
19
1
Order By: Relevance
“…We initially chose these samples as the best candidates for retaining Archean CAS because they show no sign of post-exhumation oxidation, they contain only traces of disseminated pyrite, and they display no petrographic evidence of deformation or metamorphic alteration (Paris et al, 2014), only reaching low-grade greenschist facies (Miyano and Beukes, 1984). Overall, the sulfate content of those rocks (roughly 10 to 50 ppm) is consistent with precipitation of inorganic aragonite in seawater with sulfate concentrations around 100 µmol/L or precipitation calcite at concentrations lower than 30 µmol/L (Barkan et al, 2020), a range that agrees with existing seawater sulfate concentration estimates for the Neoarchean (Crowe et al, 2014;Fakhraee et al, 2018). However, no constraints exists on dolomite, or during the aragonite-calcite diagenetic inversion (except during meteoric diagenesis, Gill et al, 2008).…”
Section: Does Post-depositional History Affect the Sulfur Isotopic Sisupporting
confidence: 75%
“…We initially chose these samples as the best candidates for retaining Archean CAS because they show no sign of post-exhumation oxidation, they contain only traces of disseminated pyrite, and they display no petrographic evidence of deformation or metamorphic alteration (Paris et al, 2014), only reaching low-grade greenschist facies (Miyano and Beukes, 1984). Overall, the sulfate content of those rocks (roughly 10 to 50 ppm) is consistent with precipitation of inorganic aragonite in seawater with sulfate concentrations around 100 µmol/L or precipitation calcite at concentrations lower than 30 µmol/L (Barkan et al, 2020), a range that agrees with existing seawater sulfate concentration estimates for the Neoarchean (Crowe et al, 2014;Fakhraee et al, 2018). However, no constraints exists on dolomite, or during the aragonite-calcite diagenetic inversion (except during meteoric diagenesis, Gill et al, 2008).…”
Section: Does Post-depositional History Affect the Sulfur Isotopic Sisupporting
confidence: 75%
“…To a major extent, sulphate is associated with the mineral part of the shell (as CAS; Dauphin et al, 2003; 2005; Fichtner et al, 2018; Perrin et al, 2017; Tamenori et al, 2014). During CAS incorporation in aragonite, the δ 34 S SO4 is enriched by 1‰ (Barkan et al, 2020). The fact that the δ 34 S CAS value in the A. islandica shell is not 1‰ higher but instead slightly lower than the primary seawater signal of 21.2‰ (Johnston et al, 2014) can be explained by a weak vital effect during CAS incorporation, causing slightly depleted values.…”
Section: Resultsmentioning
confidence: 99%
“… The shell experienced a preferential loss of low δ 34 S CAS values, and the δ 34 S CAS moved towards equilibrium with the δ 34 S SO4 of the incubation medium. Barkan et al (2020) reported an isotopic enrichment of 1‰ for δ 34 S CAS in aragonite compared to aqueous sulphate. However, because of the ongoing organic processes in and around the shell, it is purely speculative to what extent an equilibrium between aragonitic shell and medium could develop. In the anoxic sediment microbial sulphate reduction (MSR) occurred, which led to a 34 S‐enrichment in the aqueous sulphate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minor amount of sulfate is incorporated into biogenic and abiogenic carbonate phases. Biogenic carbonates often contain part‐per‐thousand sulfate by mass, while inorganic cements typically contain hundreds of parts‐per‐million (Barkan et al, 2020; Busenberg & Plummer, 1985; Giri & Swart, 2019; Paris, Fehrenbacher, et al, 2014; Staudt & Schoonen, 1995). Recent sediments from various peritidal carbonate platform environments include CAS with δ 34 S values similar to modern seawater, which suggests that marine carbonate rocks may preserve sulfate and its δ 34 S from ancient seawater (Lyons et al, 2004).…”
Section: Discussionmentioning
confidence: 99%